Evaluasi Kinerja Struktur Atas pada Gedung Kejuruan Welding BLK Ambon: Evaluation of the Superstructure Performance of the Welding Vocational Building at BLK Ambon - Achmad, Abdulazizsyah; Frans, Pieter Lourens; Siahay, Margie Civitaria (LITERA: Jurnal Ilmiah Mutidisiplin, 2024)
Ambon has a history of significant earthquakes, especially on September 26, 2019. Based on data from the National Disaster Management Agency (BNPB), the earthquake caused at least 30 deaths and widespread infrastructure damage. Therefore, building structures in Ambon City must be planned to be able to withstand earthquake loads and other dynamic loads and what the condition of the structure is when experiencing earthquake forces. This study aims to analyze and solve the structural conditions of the BLK Ambon Welding Vocational Building when exposed to earthquake forces. In this study, the author uses the spectrum response method to analyze the dynamic response of the structure to earthquake loads, and uses SAP 2000 v20 software to analyze the forces in the structure. Based on the results of the analysis of the X-direction dynamic shear force after scaling the force of 936.04 kN and the Y-direction dynamic shear force of 936.23 kN, it can be concluded that the structure is declared safe against the working loads and has met the requirements of SNI 1726-2019. And for the deviation analysis carried out, the value of the inter-floor deviation, especially for both floors in the X and Y directions, does not exceed and meets the requirements for the inter-level deviation permit, which is 67.5 mm. Based on the results of the evaluation of the level of structural performance obtained, the maximum total drift value is 0.0007 for the X direction and the Y direction is 0.0002, the results of this calculation indicate that the evaluated building is declared safe after the earthquake, damage and casualties are very limited and the building can be immediately re-used.